3D reconstruction of patient-specific femurs using Coherent Point Drift - Bin Zhang; Jinwei Sun; Zhiyong Chi; Shaobin Sun (Institute of Advanced Engineering and Science, 2013)
This paper dealt with the problem that the overlapping digital radiographs couldn`t reflect the 3D space information of the patient-specific femur in the orthopaedic surgery diagnosis. A 2D-3D non-rigid registration method based on Coherent Point Drift was proposed to realize the 3D reconstruction of the patient-specific femur before the surgery, which used biplanar digital radiographs of the patient-specific femur and the CT volume data of a generic femur. With the advantages of low cost, fast imaging speed and little radiation to the patients and doctors, this method provided more effective 3D imaging information for the femur diagnosis and preoperative plans. The registration experiments showed that the proposed method recovered the 3D model and the pose of the patient-specific femur effectively with a fast, accurate and robust registration result, which had satisfied the needs of clinical application. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2158